Diffuse cutaneous mastocytosis with novel somatic KIT mutation K509I and association with tuberous sclerosis. Issue 9 (31st July 2018) - Otani, Iris M.; Carroll, Ryan W.; Yager, Phoebe; Kroshinsky, Daniela; Murphy, Sarah; Hornick, Jason L.; Akin, Cem; Castells, Mariana; Walter, Jolan E.
Key Clinical Message: Diffuse cutaneous mastocytosis (DCM) is a rare but potentially fatal condition when diagnosis and targeted treatments are delayed. This case illustrates the life‐threatening complications in DCM and reviews the currently available treatments. To our knowledge, this is the first report of mastocytosis with somatic K509I mutation and concomitant tuberous sclerosis. Abstract : Diffuse cutaneous mastocytosis (DCM) is a rare but potentially fatal condition when diagnosis and targeted treatments are delayed. This case illustrates the life‐threatening complications in DCM and reviews the currently available treatments. To our knowledge, this is the first report of mastocytosis with somatic K509I mutation and concomitant tuberous sclerosis.